A Perbandingan Lakuan Ken Dedes pada Cerita Rakyat dan Teks Drama The Light of Ken Dedes - Nurul Hanifah; David Setiadi; Asep Firdaus (JURNAL SKRIPTA, 2026)
The folklore of Ken Arok and Ken Dedes is one of the most well-known legends from East Java, which has been adapted into various other literary forms. One such adaptation is the drama script The Light of Ken Dedes by M. Ahmad Jalidu, which features a more modern narration. This modernization highlights significant differences, particularly regarding the role of Ken Dedes in the two works. While Ken Dedes plays a more passive role (object) in the original folklore, she takes a more active role (subject) in the drama script, especially concerning the events and incidents that befall her. Therefore, the objective of this research is to compare the role of Ken Dedes in the folklore and the drama script to identify similarities and shifts in her characterization. The use of comparative literature and a feminist literary criticism approach was selected as it aligns with the focus on the shifting role of Ken Dedes in facing the patriarchal culture she experiences as the female protagonist in both works. The research methodology employed is descriptive qualitative, as the objects of study are texts, the analysis of which will be described in detail. This study reveals similarities and differences in Ken Dedes’s agency toward the events she faces, such as Ken Dedes as the arbiter of her own marriage, Ken Dedes as an object of power legitimacy, and Ken Dedes as an existential subject.